High-speed wavefront determination method based on single in-and-out electric field analysis to focus light through highly scattering medium - Cao, Jing; Yang, Qiang; Miao, Yusi; Li, Yan; Wang, Pinghe; Chen, Zhongping (APL photonics, 2021)
We develop a new type of high-speed wavefront determination method with single feedback measurement to focus light through a 15.2 scattering mean free path in ∼113 ms. Our method is based on a heterodyne-detection phase sensitivity interferometer. First, the matrix which describes the light propagation process in the sample is measured by single input and output optical fields’ analysis. Then, by using a spatial light modulator to reshape the incident light with a matched wavefront, a focused beam is observed behind the sample. The proposed high-speed light focusing method will open new spot scanning mode toward deeper imaging through highly scattering biological tissues.